Arterial stiffness as a factor of structural and functional cardiac remodeling in obesity - M. A. Druzhilov; T. Yu. Kuznetsova (Российский кардиологический журнал)
Aim. To analyze the association of parameters characterizing the degree of arterial stiffness and echocardiographic criteria for cardiac remodeling in patients with abdominal obesity.Material and methods. The study included 194 patients (men aged 46 to 55 years (49,0±2,3 years)), without hypertension (24-hour average blood pressure (BP) 117,5±5,5/73,0±4,1 mmHg), diabetes and cardiovascular diseases, with abdominal obesity (waist circumference >94 cm, body mass index 31,3±3,5 kg/m2). Lipids and glucose concentrations were evaluated, and glomerular filtration rate was estimated using the CKD-EPI equation. We conducted 24-hour monitoring of blood pressure and arterial stiffness parameters (aortic pulse wave velocity (PWV), augmentation index (AIx) and systolic BP in the aorta), and echocardiography.Results. Left ventricular (LV) hypertrophy was detected in 14 (7,2%) patients, LV diastolic dysfunction — in 36 (18,6%) patients. The correlation of the average aortic PWV and the AIx with the LV mass index and the left atrial volume was shown. Patients with a high aortic PWV exceeding the 75th percentile of distribution (8,2 m/s) were characterized by a higher incidence of hypertrophy (18,8% vs 4,9%,p<0,01) and LV diastolic dysfunction (50,0% vs 12,3%, p<0,001). Patients with/with-out LV hypertrophy and diastolic dysfunction were characterized by higher values of average 24-hour aortic PWV, AIx and systolic BP in the aorta. According to the regression analysis, the predictors of LV diastolic dysfunction were age, waist circumference, aortic PWV, and AIx.Conclusion. The relationship of parameters characterizing the degree of arterial stiffness, primarily, aortic PWV and echocardiographic parameters of the structural and functional cardiac remodeling in obese patients was revealed. Patients with a high aortic PWV (>8,2 m/s for men aged 46-55 years) are characterized by a higher prevalence of LV hypertrophy and diastolic dysfunction, as well as left atrial dilatation. This association is probably a reflection of one of the many pathogenesis links of HF and supraventricular cardiac arrhythmias in obese patients.